Comparative in vitro study of root roughness after instrumentation with ultrasonic and diamond tip sonic scaler Estudo comparativo in vitro da rugosidade radicular após instrumentação com ultrassom e pontas sônicas diamantadas - Fernanda Vieira Ribeiro; Renato Correa Viana Casarin; Francisco Humberto Nociti Júnior; Enilson Antônio Sallum; Antonio Wilson Sallum; Márcio Zaffalon Casati (University of São Paulo, 2006)
OBJECTIVE: The purpose of this study was to evaluate the root surface roughness after instrumentation with hand curette and diamond-coated sonic and universal ultrasonic tips. MATERIALS AND METHODS: Forty root surfaces of human teeth were randomly assigned to four treatment groups: control group (without instrumentation), curette instrumentation, ultrasonic instrumentation with universal tip and sonic instrumentation with diamond-coated tip. Each sample was instrumented with fifteen strokes. Before and after instrumentation, surface roughness was measured. In addition, the root surface topography was examined after treatment under the scanning electron microscope. RESULTS: Significant statistical differences (p <0.05) were observed when comparing the control group (0.48±0.07mm) to the treated groups (hand - 1.246±0.279mm, ultrasonic - 1.468±0.177mm and sonic instrumentation - 1.576±0.20mm). The highest roughness was produced by diamond-coated sonic tip and by ultrasonic universal tip (p >0.05). CONCLUSION: The diamond-coated tip with sonic scaler instrumentation and ultrasonic instrumentation produce similar root surface roughness, higher than curette instrumentation. OBJETIVO: O objetivo do presente estudo foi avaliar a rugosidade radicular obtida após instrumentação por aparelho sônico com pontas diamantadas, curetas e ultrassom. MATERIAL E MÉTODOS: Quarenta superfícies radiculares, devidamente polidas e incluídas em resina acrílica, foram dividas em 4 grupos de tratamento: grupo controle (sem instrumentação) e instrumentação com cureta Gracey 5/6, ultrassom ou aparelho sônico com ponta diamantada. Em cada amostra foram realizados 15 movimentos de raspagem. Antes e após esta instrumentação foi utilizado um rugosímetro para a medição da rugosidade radicular. Além disso, a topografia da superfície radicular foi avaliada após o tratamento com microscopia eletrônica de varredura. RESULTADOS: Diferenças estatisticamente significantes (p<0.05) foram observadas ao se comparar o grupo controle (0.48±0.07mm) aos grupos tratados (cureta - 1.246±0.279mm, ultrassom - 1.468±0.177mm e aparelho sônico com ponta diamantada - 1.576±0.20mm). As maiores rugosidades foram produzidas pela ponta sônica diamantada e ponta universal de ultrassom (p>0.05). CONCLUSÃO: A instrumentação sônica com pontas diamantadas promove uma rugosidade radicular equivalente à instrumentação com ultrassom, sendo essa rugosidade superior àquela apresentada pela instrumentação manual.